Estimation of mangrove sedimentary carbon stock in Deah Raya, Banda Aceh - Khairunnisa, Khairunnisa; Rahayu, Adisty; Haridhi, Haekal Azief; Farahisah, Harum; Ulfah, Maria (Depik Jurnal Ilmu Ilmu Perairan, Pesisir, dan Perikanan, 2025)
Mangrove ecosystems are important blue carbon sinks, particularly through long-term carbon storage in their sediments. This study examined sediment bulk density, organic carbon content, and sediment carbon stock in the mangrove ecosystem of Deah Raya Village, Banda Aceh, Indonesia, which has regenerated following the 2004 Indian Ocean tsunami. Sediment samples were collected at three depth intervals (030 cm, 3060 cm, and 60100 cm) across three stations. Organic carbon content was determined using the Loss on Ignition (LOI) method, and carbon stock was estimated based on bulk density and carbon concentration.Bulk density ranged from 0.52 to 0.93 g cm and increased with depth, reflecting greater sediment compaction and lower organic matter accumulation. Organic carbon content varied across depths and stations, with the highest value (4.77%) recorded at Station 3 at 3060 cm, likely due to fine root biomass and reduced decomposition in anoxic layers. Sediment carbon stock ranged from 14.81 to 29.20 Mg C/ha, which is lower than national and global averages for mature mangrove systems, indicating limited carbon accumulation in this recovering ecosystem. These findings highlight the influence of vegetation structure and sediment characteristics on blue carbon storage and underscore the need for continued protection to enhance future carbon sequestration capacity.Keywords:MangroveSedimentCarbonBanda Aceh